Organic Syntheses 2003
DOI: 10.1002/0471264180.os069.15
|View full text |Cite
|
Sign up to set email alerts
|

Propargylation of Alkyl Halides: ( E )‐6,10‐dimethyl‐5,9‐undecadien‐1‐yne and ( E )‐7,11‐dimethyl‐6,10‐dodecadien‐2‐yn‐1‐ol

Abstract: Propargylation of alkyl halides: ( E )‐6,10‐dimethyl‐5,9‐undecadien‐1‐yne and ( E )‐7,11‐dimethyl‐6,10‐dodecadien‐2‐yn‐1‐ol product: (E)‐6,10‐dimethyl‐5,9‐undecadien‐1‐yne byproduct: 2‐butyn‐1‐ol product: (E)‐7,11‐dimethyl‐6,10‐dodecadien‐2‐yn‐1‐ol reactant: trimethylsilyl‐protected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…10 An indirect procedure employing 3-lithio-1-trimethylsilylpropyne initially produces the trimethylsilylprotected acetylene, from which the required homologated alkyne is liberated by reaction with ethanolic silver nitrate followed by sodium cyanide. 11 We previously reported 12 the preparation of the operational equivalent of the propargyl dianion (5) from treatment of allene (6) with 2 equiv of n-BuLi (Scheme 2). This dianion (5) regiospecifically reacted with aromatic aldehydes and ketones to produce homopropargyl alcohols (3) in very good yields (Scheme 2, method A).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 An indirect procedure employing 3-lithio-1-trimethylsilylpropyne initially produces the trimethylsilylprotected acetylene, from which the required homologated alkyne is liberated by reaction with ethanolic silver nitrate followed by sodium cyanide. 11 We previously reported 12 the preparation of the operational equivalent of the propargyl dianion (5) from treatment of allene (6) with 2 equiv of n-BuLi (Scheme 2). This dianion (5) regiospecifically reacted with aromatic aldehydes and ketones to produce homopropargyl alcohols (3) in very good yields (Scheme 2, method A).…”
Section: ■ Introductionmentioning
confidence: 99%
“…13 An additional advantage of this methodology is that the initially formed lithium acetylide intermediate (7) may be further transformed, in situ, into other derivatives (8) by adding electrophiles such as paraformaldehyde, iodomethane, trimethylsilyl chloride, and ethyl chloroformate. 12,14 When this methodology was used with aliphatic aldehydes or ketones, mixtures of allenic and acetylenic isomers, favoring the latter (2:8), were obtained. Fortunately, we found that these mixtures of allenyl and homopropargyl alcohols can be quantitatively converted to the corresponding homopropargyl alcohols by a zipper reaction.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The reaction was warmed to room temperature and stirred for 5 h. Sat. 37 (2E)-3-Bromo-7-methylocta-2,6-dien-1-ol (4a). NaCl (50 ml) was added and the solution was extracted with petroleum ether (3 × 50 ml).…”
Section: Modelling Studiesmentioning
confidence: 99%
“…R f 0.40 (1 : l hexanesether); data: (lit. 37 ) 1 H NMR (400 MHz, CDCl 3 ) δ: 5.16 (m, 1H), 5.09 (m, 1H), 4.25 (d, 2H, J = 10.8), 2.22 (narrow m, 4H), 2.07 (m, 2H), 1.99 (m, 2H), 1.68 (s, 3H), 1.61 (s, 3H), 1.60 (s, 3H), 1.50 (t, 1H, J = 10.8), 13 C NMR (400 MHz, CDCl 3 ) δ: 133. (2E)-3-Bromo-7-methylocta-2,6-dien-1-ol (4a).…”
Section: Modelling Studiesmentioning
confidence: 99%
“…Further useful dianions can be generated from ketones (C=C(OM)CM or C=C(OM)CCM) [138][139][140][141][142], carboxylic acids (C=C(OM) 2 ) [143][144][145], succinic acid derivatives ((C=C(OM)OR) 2 ) [146], alkynes (MC"CCM, MC"CC-OM) [147][148][149][150][151][152][153][154][155], imidazoles [156], thiophenes [157,158], b-alanine derivatives (MN-CC=C(OM)X) [159], 3-nitropropanoates [160,161], 3-hydroxypropanoates [162,163], 2-hydroxyethylsulfones [164,165], arenes [166][167][168], allenes [169], thioamides [170], and sulfonamides (MC-SO 2 NM [171]; R 2 NSO 2 -CM 2 [172]). If the nucleophilic sites in the polyanion have different chemical hardness, regioselective alkylation can be achieved by selecting a soft or a hard electrophile (second reaction, Scheme 5.13).…”
Section: 36mentioning
confidence: 99%